2016
DOI: 10.1080/01942638.2016.1247938
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Aquatic Intervention on Gross Motor Skills in Children with Cerebral Palsy: A Systematic Review

Abstract: Evidence on aquatic interventions for ambulatory children with CP is limited. Aquatic exercise is feasible and adverse effects are minimal; however, dosing parameters are unclear. Further research is needed to determine aquatic intervention effectiveness and exercise dosing across age categories and GMFCS levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 33 publications
2
46
0
5
Order By: Relevance
“…The findings of this scoping review in relation to session time, session frequency and treatment program duration corroborate the systematic review by Roostaei et al 41 in individuals with cerebral palsy, which reports greater effectiveness in sessions of 45-60 minutes for two to three times a week, for at least six weeks, and which can last for 16 weeks.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The findings of this scoping review in relation to session time, session frequency and treatment program duration corroborate the systematic review by Roostaei et al 41 in individuals with cerebral palsy, which reports greater effectiveness in sessions of 45-60 minutes for two to three times a week, for at least six weeks, and which can last for 16 weeks.…”
Section: Discussionsupporting
confidence: 87%
“…Previous experience in water is a factor to be considered for studies on this environment, as individuals who are familiar with and feel comfortable in water participate more intensively in the proposed activities compared with those less adapted 41 . Fragala-Pinkham, Haley and O'Neil 42 confirmed that children more adapted to the aquatic environment were able to exercise for a longer time within the target HR.…”
Section: Discussionmentioning
confidence: 99%
“…46 A recent SR without MA reported aquatic exercise was effective for improving motor skills in children with cerebral palsy. 47 Depending on the patient's physical characteristics and symptoms, BT and ST may contribute to pain reduction (including reduction of analgesic and/or NSAID consumption), improved QoL, and improved function in a variety of potential diseases.…”
Section: Current Evidence and Research Challengesmentioning
confidence: 99%
“…Another important aspect is the mode of the training intervention. Although systematic reviews have endorsed the effectiveness of aquatic physiotherapy and water-based exercise for people with CP (Roostaei, Baharlouei, Azadi, & Fragala-Pinkham, 2017), we are unaware of any studies which have quantified the effects of performance-focused swimming training. By definition, a valid performance-focused swimming training programme must lead to improvements in swimming performance.…”
Section: Discussionmentioning
confidence: 99%